The Effect of Metformin on Thyroid-Associated Serum Hormone Levels and Physiological Indexes: A Meta-Analysis - Wang, Junjie; Gao, Jinghan; Fan, Qin; Li, Hongzhuo; Di, Yunhua (Current Pharmaceutical Design, 2019)
Background: Many diseases can be treated with metformin. People with serum thyrotropin (TSH) levels higher than 10 mIU/L are at a risk of cardiovascular events. Some studies have suggested that metformin can lower serum TSH levels to a subnormal level in patients with hyperthyrotropinaemia or hypothyroidism. Objective: The objective of this analysis is to evaluate the effect of metformin treatment on serum TSH, free triiodothyronine (FT3), and free thyroxine (FT4) levels and other associated physiological indices. Methods: A comprehensive search using the PubMed, EMBASE, Web of Science and Cochrane Central databases was undertaken for controlled trials on the effect of metformin on serum TSH, FT3, and FT4 levels and associated physiological indices. The primary outcome measures were serum TSH, FT3 and FT4 levels, thyroid size, thyroid nodule size, blood pressure, heart rate, body weight, and body mass index (BMI). The final search was conducted in April 2019. Results: Six RCTs were included. A total of 494 patients met the inclusion criteria. Metformin treatment did not significantly lower the serum TSH levels at 3 or 6 months but did at 12 months. Moreover, forest plots also suggested that metformin can significantly lower the serum TSH levels in patients with normal thyroid function but cannot statistically change the serum TSH levels in patients with abnormal thyroid function. In addition, metformin treatment clearly lowered the serum FT3 levels and had no significant effect on serum FT4 levels. Lastly, metformin cannot significantly change the systolic blood pressure (SBP) or BMI but can clearly increase the diastolic blood pressure (DBP). Conclusion: Metformin treatment can significantly lower the serum TSH levels, and this effect was much clearer after a 12-month treatment duration and in people with normal thyroid function. However, metformin cannot significantly change the serum FT4 levels or lower serum FT3 levels in people with non-thyroid cancer diseases. In addition, metformin can significantly increase DBP, but it has no clear effect on SBP or BMI.
Keywords: hyperthyrotropinaemia